Strategies of Islamist Extremism in Europe - Mares, Miroslav (International Studies. Interdisciplinary Political and Cultural Journal, 2015)
This paper explains various strategies of contemporary Islamists extremism in Europe. The author identifies the most important variants of Islamist extremism and deals with their goals and with strategic approaches how to achieve these goals. Quasi-legalist strategies as well as violent forms of interest-empowerment are described. The author uses sources from various Islamist organizations and analyses these materials within the framework of modern insurgency. A comprehensive outlook and threat assessment of Islamist extremist strategies are included in this article.